Analisis Aspek Perbedaan Individual Dalam Psikologi Pendidikan - Lubis, Ahmad Taufiq; Syahfitra, Hidayah; Deantika, Kifty; Dalimunthe, Putri Ani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In essence, no two individuals are the same, both psychologically and physically. Including students' abilities as individuals, also different from each other. Demanding the same learning activities or processes and learning outcomes from each student essentially denies the existence of individual differences. Individual differences are currently often found in the school environment. Even the study rooms and facilities for ordinary students are different from superior students. Excellent students also often have a higher social status than ordinary students. So in this research, aspects of individual differences in educational psychology will be discussed including physical-motor differences, intelligence differences, language proficiency differences, psychological differences, personality differences, learning style differences, biological differences. Considering the importance of understanding individual differences, especially for teaching staff, this research aims to ensure that Arabic language educators can realize that it is very important to study individual differences in order to increase the effectiveness and creativity of Arabic language learning that takes place in the classroom, and also so that the community and students can understand about individual differences. The method used in this research is a qualitative research method and literature review. The results of this research show aspects of individual differences in educational psychology.